Emerging trends and hotspots in the links between the gut microbiota and MAFLD from 2002 to 2021: A bibliometric analysis - Li, Yixuan; Zhou, Yanyu; Wang, Liya; Lin, Xiaoqi; Mao, Menghan; Yin, Suqing; Zhu, Ling; Jiao, Yingfu; Yu, Weifeng; Gao, Po; Yang, Liqun (Frontiers in Endocrinology, 2022)
Background: The prevalence of metabolic associated fatty liver disease (MAFLD) presented a booming growth over recent years in the whole world. MAFLD was associated with a higher risk of end-stage liver disease, hepatocellular carcinoma and liver transplantation. Accumulating evidence indicated that gut microbiota and MAFLD were interrelated and interacted with each other. However, to the knowledge of the authors, no bibliometric quantitative analysis has been carried out to evaluate the links between the gut microbiota and MAFLD. This study aimed to use bibliometric analysis to evaluate current publication trends and hotspots in the links between the gut microbiota and MAFLD, in order to advance research in this field. Methods: The articles regarding the links between gut microbiota and MAFLD from 2002 to 2021 were identified from the Science Citation Index-Expanded of Web of Science Core Collection. CiteSpace software, Vosviewer, the R package “bibliometrix” and the Online Analysis Platform of Literature Metrology were used to analyze current publication trends and hotspots in this field. Results: A total of 707 articles were retrieved regarding the links between gut microbiota and MAFLD from 2002 to 2021. The USA occupied the leading role until 2015 and the dominance of China started in 2016. The USA was the most frequently involved country in international cooperation. Shanghai Jiao Tong University was the most productive institution. Ina Bergheim was the most productive author, publishing 14 articles. The co-citation keywords cluster label displayed ten main clusters: probiotics, bile acid, immune function, adolescents, nutritional genomics, high fat diet, systems biology, lipopolysaccharides, phosphatidylcholine, and oxidative stress. Keyword bursts analysis indicated that diet induced obesity, metabolic syndrome, ppar alpha, and lactobacillus were the research hotspots with high strength. Conclusion: The number of publications covering the links of gut microbiota and MAFLD increased dramatically in the past decade and especially became exponential growth in the last 3 years. Probiotics and bile acid will be the research direction of great importance in the etiology and novel treatment for MAFLD. This study provided systematic information and instructive assistance for future research work, that helped to discover the mechanisms and new treatments of MAFLD.